ANALISIS EFEKTIVITAS PENGGUNA APLIKASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) PADA KANTOR KECAMATAN PENUKAL MENGGUNAKAN METODE END-USER COMPUTING SATISFACTION (EUCS) - Saputra, Ari (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to analyze the effectiveness of using the Population Administration Information System (SIAK) application at the Penukal District Office. This research uses a quantitative approach. Quantitative research is an approach that prioritizes aspects of measurement and calculation in every stage of research, from planning, data collection, to analyzing results and drawing conclusions. This approach aims to measure the level of satisfaction of SIAK application users using the End-User Computing Satisfaction (EUCS) model. The survey method was chosen because it can provide measurable data regarding user perceptions and satisfaction levels with the application. The study used the End-User Computing Satisfaction (EUCS) method to measure the level of user satisfaction. The results showed that the use of the SIAK application has increased the effectiveness of population administration, but there are still some obstacles in its use. This study provides recommendations for improvement and development of the SIAK application to increase user satisfaction and the effectiveness of population administration.